A systematic review of the association between coping strategies and quality of life among caregivers of children with chronic illness and/or disability - Alana Fairfax; Jamie Brehaut; Ian Colman; Lindsey Sikora; Alessia Kazakova; Pranesh Chakraborty; Beth K. Potter; in collaboration with the Canadian Inherited Metabolic Diseases Research Network (BMC, 2019)
Abstract Background Parents of children with chronic illness have reported decreased psychological and physical quality of life (QoL) relative to parents of children without such illness, which may be associated with the extent of complexity involved in the caregiving role. Given that coping strategies have been reported to influence QoL, our goal was to synthesize existing research about the association between coping strategies and QoL in caregivers of children with chronic illness. We were particularly interested in whether coping strategies may mediate the association between caregiving complexity and QoL, or may modify the association. Methods We developed an electronic search strategy to identify relevant citations in Medline, EMBASE, PsycINFO and CINAHL. Two reviewers independently assessed retrieved citations against pre-specified inclusion criteria in two stages of screening. One reviewer abstracted data on study characteristics, methods to address confounding, measurement tools, risk of bias, and results with respect to associations of interest. A second reviewer validated extracted data. We summarized results narratively. Results 2602 citations were screened and 185 full-text articles reviewed. The 11 articles that met inclusion criteria addressed 5 diseases and included a total of 2155 caregivers. Ten of the 11 included studies were cross-sectional. We identified some evidence that coping was associated with QoL: in three studies, coping strategies considered to be adaptive were positively associated with psychological QoL while in one study, maladaptive strategies were negatively associated with psychological QoL. Only two studies considered coping as a potential mediating variable in the association between caregiving complexity and parental QoL, with inconsistent findings and challenges in interpreting cross-sectional associations. No studies considered coping as a moderating variable. The variability among instruments used to measure key constructs, particularly coping strategies, made it difficult to synthesize results. Conclusions We found that coping strategies may be associated with psychological QoL among parents of children with chronic illness. We also identified important research gaps related to the consistent and clear measurement of coping strategies and their prospective association with QoL. Understanding how coping strategies are associated with QoL is important to inform the development of interventions to support families of children with chronic illness.